2009
DOI: 10.1161/strokeaha.108.540161
|View full text |Cite
|
Sign up to set email alerts
|

Response to Letter by Sharma et al and Leibeskind

Abstract: Response to Letter by Sharma et al and LeibeskindResponse:We would like to thank Dr Sharman et al and Dr Liebeskind for their interest in our recent publication in which presence of a right-to-left shunt was associated with dramatic improvement after thrombolytic therapy in acute ischemic stroke patients. We demonstrated that tissue plasminogen activator (t-PA) thrombolysis was more effective in stroke patients with a right-to-left shunt than in patients without a right-to-left shunt. We believed that the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…There is also controversy about the rate of recanalization after thrombolysis in AF patients. Some studies have found similar [11], lower [4], or even higher recanalization rates in the AF population compared to non-AF [22]. Differences in clot organization and collagen composite can affect responses to medical or mechanical reperfusion therapy [18,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also controversy about the rate of recanalization after thrombolysis in AF patients. Some studies have found similar [11], lower [4], or even higher recanalization rates in the AF population compared to non-AF [22]. Differences in clot organization and collagen composite can affect responses to medical or mechanical reperfusion therapy [18,23].…”
Section: Discussionmentioning
confidence: 99%
“…This was not observed in patients with mild stroke [3]. Other studies have shown that AF is an independent predictor of no recanalization after thrombolysis [4]. Tu et al suggested that the worse stroke outcome in AF may be explained by more severe hypoperfusion, infarct growth, and hemorrhagic transformation [5].…”
Section: Introductionmentioning
confidence: 96%
“…We introduced non-volatile logic to widen FeRAM application [3]. By using this technology, instant boot and zero standby power are easily realized because the LSI chip retains logic states without continuous power supply [4].…”
Section: Introductionmentioning
confidence: 99%